Distribution patterns, migration route and Phylogenetic relationship of waders (aves: Scolopacidae) in Sarawak, Malaysian Borneo - Nurul Ashikeen, Ab Razak (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Among birds, the order Charadriiformes are considerably well-studied but taxonomic and phylogenetic information at the intra family level are still lacking. The main focus of this study is to describe the evolutionary traits within Scolopacidae species (waders) with inference on their macrogeographic distributional pattern in Southeast Asian region, particularly in Sarawak. This study consists of two main research components. The first is the macrogeographical distribution of Scolopacids in Southeast Asian region and their habitat utilization derived from regional avian database (eg: Bird field guides, published reports and surveys). The data analysis was illustrated by comparative Unweighted Pair Group Method with Arithmetic Mean (UPGMA) on species distribution and their habitat preferences. Essentially, the general distribution pattern of shorebirds within the Southeast Asian countries was also presented with emphasis on the specific distribution of the Scolopacidae species during non-breeding season along the East-Asian Australasian Flyway (EAAF). The second component is the reconstruction of phylogenetic relationship of Scolopacidae species using two different markers; the mitochondrial DNA Cytochrome Oxidase I (COI) and the nuclear DNA Recombinant Activating Gene 1 (RAG1). Overall, 16 species of Scolopacidae were sampled from six selected sampling sites across Sarawak. These include Lundu, Asajaya, Buntal, Sungai Aur, Kampung Chupak and Pulau Bruit. The phylogenetic trees were constructed using four inference methods; Neighbour-Joinning (NJ), Maximum Parsimony (MP), Maximum Likelihood (ML), and Bayesian Inference (BI). In general, the result from my first component revealed that shorebirds as well as waders are widely dispersed throughout Southeast Asian countries although their distributional patterns were slightly different. This is further demonstrated by the dendrogram clustering of waders where Burma was separated from other Southeast Asian countries. Whereas, for dendrogram of shorebirds; vi Burma, Vietnam and Thailand were clustered together as a group. Hence, the distributional patterns are consistent with the recent tectonic plates that consist of mainland and island formations. In addition, waders performed migration using unique and specific pathways within East Asian Australasian Flyway (EAAF). Within their pathways, waders exhibited specific preferences in selecting the most fitting and suitable habitat for feeding and roosting. This is perhaps best modelled by subfamily Scolopacinae (snipe) in which this particular inland group is potentially a habitat specialist rather than a habitat generalist group. On the other hand, the molecular evidences for both DNA genes and combined genes revealed consistent tree topology groupings of two major clades, which are large sandpipers (Numeniinae) derived as the basal lineage and another group consisting of small to medium sandpipers (Calidriinae, Scolopacinae, and Tringinae). Within all phylogenetic trees, Bayesian inference (BI) from combined genes displayed the most resolved tree of all inference methods. As a whole, the evolutionary patterns of genetic traits within the Scolopacidae family were plausibly incongruent with their specific distribution and habitat preferences. This is shown by the cluster analysis depicting that the Scolopacinaes were clearly isolated from the others. On the contrary, this group was closely related to Tringinae in the phylogenetic trees. Although both are genetically related, they have probably evolved different morphological features that permitted them to adapt in suitable habitat.